MOTIVASI BELAJAR GURU PAUD DI TK NEGERI PEMBINA KARANGAN DALAM PELAKSANAAN PEMBELAJARAN SELAMA PANDEMI - Nuryanti Nuryanti; Hanita Hanita; Rizqi Syafrina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2022)
Based on government regulations regarding the implementation of learning during the pandemic by learning from home. So PAUD teachers must be able to innovate in carrying out learning activities through online and offline learning according to directions from the government. This study aims to determine the implementation of PAUD teacher learning motivation in Pembina Karangan State Kindergarten during the pandemic. This study uses a qualitative approach, with data collection through observation, interviews, and documentation. The subject of the study was a Kindergarten teacher at Pembina Karangan. From the results of the analysis, it is known that the implementation of learning during the pandemic is increasing as a form of achievement motivation during the pandemic. This achievement is supported by aspects of perseverance, independence, struggle, and consistency in expressing opinions.